Technological properties of sour cassava starches: Effect of fermentation and drying processes. (July 2018) - Díaz, Andrea; Dini, Cecilia; Viña, Sonia Z.; García, María Alejandra
Abstract: Cassava sour starch is a naturally-fermented, sun-dried product. It allows obtaining less dense bakery products than the native starch, being an appreciated gluten-free ingredient. The aim of this work was to study the effect of fermentation and drying method on the physicochemical and technological characteristics of cassava sour starch and to identify the relationships among those distinctive features that may condition their potential food applications. Natural fermentation following starch extraction could not be replaced by the use of a starter. Sour starches pastes showed lower apparent viscosities related to their lactic and/or butyric acid content, and a higher retrogradation tendency, mainly associated to sun-drying. The fermentation combined with the solar exposition represent a complex process that induce changes not easily observed on starch powders but clearly evidenced after gelatinization of the starch suspensions. Graphical abstract: Highlights: Effects of fermentation and drying-methods on cassava starches were studied. Organic acid profiles evidenced different microbiota and/or fermentation paths. Sour starch pastes showed lower viscosities and a higher retrogradation tendency. 1048:1023 ATR peak ratios of fermented starch pastes were increased after storage. Relationships among distinctive sour starches features were identified by PCA.